Group guidance as an alternative method to building religious character - Sutarto, Sutarto; Sari, Dewi Purnama (Universitas Islam Negeri Raden Intan Lampung, 2020)
This article is aimed to determine the effectiveness of group guidance in improving understanding, attitudes, and practice of religious character values in the aspects of faith, worship, morals, and muamalah. The method used was an experiment with a pretest-posttest control group design. The population consisted of 137 people. The number of samples was 30 students with a general school or junior high school education background. Fifteen students were taken as the experimental group, and fifteen others were taken as the control group. Samples were taken by purposive sampling technique. Data were collected using a questionnaire and analyzed using SPSS 16.0 for windows. The results of the study showed that the average score of the experimental group was higher than the control group. The t-test results also showed that group guidance could significantly improve understanding, attitudes, and practice of religious character values. This means that group guidance can be used as an alternative method for building religious character. This article is aimed to determine the effectiveness of group guidance in improving understanding, attitudes, and practice of religious character values in the aspects of faith, worship, morals, and muamalah. The method used was an experiment with a pretest-posttest control group design. The population consisted of 137 people. The number of samples was 30 students with a general school or junior high school education background. Fifteen students were taken as the experimental group, and fifteen others were taken as the control group. Samples were taken by purposive sampling technique. Data were collected using a questionnaire and analyzed using SPSS 16.0 for windows. The results of the study showed that the average score of the experimental group was higher than the control group. The t-test results also showed that group guidance could significantly improve understanding, attitudes, and practice of religious character values. This means that group guidance can be used as an alternative method for building religious character.